DISCOURSE MARKERS IN MICHELLE OBAMA’S INTERVIEW DURING OPRAH’S 2020 VISION TOUR VISIONARIES - Tsuroyya, Inas; Degaf, Agwin (Annual International Conferences on Language, Literature, and Media, 2023)
The objective of this study revolves around a meticulous analysis of a 2020 interview session featuring Michelle Obama and Oprah Winfrey. It seeks to delineate the prevalent discourse marker types and their nuanced functions in this conversation. Employing a qualitative approach, the researchers scrutinized the interview data to extract valuable insights. The outcomes of this analysis unearthed a remarkable total of 957 instances of discourse markers, spanning across all ten types and fulfilling each of the six designated functions. To provide a more detailed breakdown, the instances consisted of 21 interjections, while no instances of greetings and farewell expressions were identified. Moreover, 454 instances of linking adverbials, 108 instances of stance adverbials, one instance of vocatives, 13 instances of response elicitors, 350 instances of response forms, five instances of hesitators, two instances of various polite speech-act formulations, and three instances of expletives were observed. Remarkably, it became evident that Oprah Winfrey consistently refrains from employing greeting and farewell expressions in her video interviews, indicating a deliberate stylistic choice on her part. Despite this unique pattern, the discourse markers, in alignment with their diverse types and functions, wield considerable influence in enhancing the audience's comprehension of the interview's content. Skillful deployment of these markers facilitates seamless information flow, reinforces connections, establishes causal relationships, and offers temporal context, enriching the viewer experience.